Balancing the imperatives of nationbuilding and the lofty aspirations for democracy: South Sudan’s long and difficult road to democratic immortality - Dau, Santino Ayuel Longar (Frontiers in Political Science, 2025)
Pursuant to the 2018 Agreement, South Sudan is set to go to the polls in December, 2026, marking the world’s youngest country’s first ever democratic election since independence. Using both qualitative and quantitative analyses, this article evaluates the country’s institutional readiness for this transformative exercise as well as examines, more broadly, the historicity of democracy, having regard to the timeliness of transplanting democracy in South Sudan and the country’s fragile socio-politico-economic structures. The article finds that South Sudan’s low GDP per capita, low literacy rate, heavy dependence on oil revenues, lack of vibrant middle class and civil society organizations, inability to sustain institutions of democracy as well as its post-conflict state fragility, renders it unable to attain liberal democracy. To arrive at this conclusion, the article appraises, a priori, the relationship between a nation’s level of economic development and democracy, having regard to the empirical findings that non-democratic countries that solely rely on natural resources for their economic development, rather than on economic growth berthed at the pier of capitalist ingenuity, tend to retard their transition to liberal democracy. It follows that, in order to appreciate (a) whether South Sudan’s current socio-economic and political climate mirrors the models of developing countries that have successfully transitioned into liberal democracies;(b) whether the upcoming elections could usher in the country’s era of sustainable transition to liberal democracy; or (c) whether such elections are purely a veneer of democracy; the article systematically analyzes the country’s current socio-economic and political conditions vis-à-vis its potential to leapfrog to liberal democracy and, therefore, achieve democratic immortality. In light of these material realities in South Sudan as well as the importance of balancing the inherent trade-off between the imperatives of nationbuilding and the ‘dark sides’ of democracy, the article concludes that the efforts to adopt democracy, at this stage, could only leave South Sudan deeply entangled in illiberal democracy-at least in the short run.